Orthotopic heart transplantation with reconstruction of persistent left superior vena cava - Kazuma Handa; Hiroki Hata; Koichi Toda; Shigeru Miyagawa; Yasushi Yoshikawa; Daisuke Yoshioka; Yoshiki Sawa (Surgical Case Reports, 2020)
Abstract Background Persistent left superior vena cava is a not uncommon congenital vascular abnormality. We report a case of heart transplantation with reconstruction of persistent left superior vena cava using a prosthetic vascular graft. Case presentation A 20-year-old man with idiopathic dilated cardiomyopathy and persistent left superior vena cava underwent orthotopic heart transplantation 2 years and 3 months after left ventricular assist device implantation. Because the persistent left superior vena cava had a larger diameter than the right superior vena cava, the transected persistent left superior vena cava was reconstructed with a prosthetic vascular graft anastomosed to the free wall of the right atrium. Postoperative enhanced computed tomography revealed good patency of the graft. The patient’s postoperative course has been uneventful during 2 years of follow-up, despite the risk of complications. Conclusions Reconstruction of a persistent left superior vena cava with a prosthetic vascular graft may be one option at the time of heart transplantation.